ANALYSIS THE PROCESS OF KNOWLEDGE MANAGEMENT AT PT. MEARES SOPUTAN MINING LIKUPANG - Kauwo, Faldy Marcel (Universitas Sam Ratulangi, 2016)
The quality of the employee should be in the top priority of consideration. The objective of this study is to analyze the process of employee knowledge management at PT. MSM Likupang. The population observed is employees in PT. MSM as many as 7 informants. The results based on data collection method processed using the Non-Structural Interview due to its ability to capture both human and situational influences impacting on the social phenomena and to provide additional insights based on the recognition of the value. In conclusion, the company emphasizes knowledge management as a part of their organizational activity and applies the knowledge management standard processes, the knowledge management activities supported by some experts, the company provides self-learning, the company creates team learning called PAS (Positive Attitude Safety), and the company required sharing activity to create a sustainable distribution of new knowledge. Keywords: human resource management, knowledge management